IDENTIFICATION OF CRITICAL POINTS OF TRACEABILITY IN FROZEN CUBE TUNA USING FMECA METHOD IN TUNA FREEZING COMPANY - Muh Suryono; Aulia Azka; Kurnia Sada Harahap; Reza Fadilah (Politeknik Kelautan dan Perikanan Dumai, 2023)
The use of traceability systems in the food industry is very important for performing search actions in the event of a product withdrawal. The use of the FMECA method in evaluating the level of efficiency and effectiviveness of the traceability system, through the possibility of failures that arise in the traceability sytem implemented. Data analysis was perfomed based on an expert system using the FMECA method. The result of the FMECA conducted on the traceability management system there are 27 points of failure, each function has local effects and global effects. The results recorded from the FMECA analysis show that there are 11 critical points in the acceptable without revision area, 13 points are in the acceptable area with revision, and 2 points are in the undesirable area. The traceability of frozen tuna products at tuna freezing companies has been going well with 2 traceability critical points.